Stem and progenitor cells of the mammalian olfactory epithelium: Taking poietic license. Issue 4 (27th September 2016) - Schwob, James E.; Jang, Woochan; Holbrook, Eric H.; Lin, Brian; Herrick, Daniel B.; Peterson, Jesse N.; Hewitt Coleman, Julie
ABSTRACT: The capacity of the olfactory epithelium (OE) for lifelong neurogenesis and regeneration depends on the persistence of neurocompetent stem cells, which self‐renew as well as generating all of the cell types found within the nasal epithelium. This Review focuses on the types of stem and progenitor cells in the epithelium and their regulation. Both horizontal basal cells (HBCs) and some among the population of globose basal cells (GBCs) are stem cells, but the two types plays vastly different roles. The GBC population includes the basal cells that proliferate in the uninjured OE and is heterogeneous with respect to transcription factor expression. From upstream in the hierarchy to downstream, GBCs encompass 1) Sox2 + /Pax6 + stem‐like cells that are totipotent and self‐renew over the long term, 2) Ascl1 + transit‐amplifying progenitors with a limited capacity for expansive proliferation, and 3) Neurog1 + /NeuroD1 + immediate precursor cells that make neurons directly. In contrast, the normally quiescent HBCs are activated to multipotency and proliferate when sustentacular cells are killed, but not when only OSNs die, indicating that HBCs are reserve stem cells that respond to severe epithelial injury. The master regulator of HBC activation is the ΔN isoform of the transcription factor p63; eliminating ΔNp63 unleashes HBC multipotency. Notch signaling, via Jagged1 ligand on Sus cells and Notch1 and Notch2 receptors on HBCs, is likely to play a major role in setting the level of p63 expression. Thus, ΔNp63 becomes a potential therapeutic target for reversing the neurogenic exhaustion characteristic of the aged OE. J. Comp. Neurol. 525:1034–1054, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The authors review what is known of progenitors in the olfactory epithelium and describe the persistence of two distinct categories of stem cells, horizontal basal cells (HBCs), which are late to develop and dormant in the absence of injury, and some among the population of globose basal cells (GBCSTEM ), which are normally mitotic and productive and resemble the cells of the olfactory placode. The interchange between GBCs that act as stem cells (GBCs that are multipotent [GBCMPP ]) and the HBC reserve stem cells occurs in response to complex regulation, but the transition to and from HBCs critically depends on the transcription factor p63.